Performance of the London Atlas, Willems, and a new quick method for dental age estimation in Chinese Uyghur children - Yueting Lin; Nuerbiyamu Maimaitiyiming; Meizhi Sui; Nuerbiya Abuduxiku; Jiang Tao (BMC Oral Health, 2022)
Abstract Background Numerous dental age estimation methods have been devised and practised for decades. Among these, the London Atlas and Willems methods were two of the most frequently adopted, however dependent on atlantes or tables. A new estimation method less reliant on external measurement could be efficient and economical. Aim This study aimed to evaluate the utility and applicability of the dental age estimation methods of London Atlas, Willems, and a new quick method that subtracts the number of developing teeth from the universal root mature age of 16 years in one of the lower quadrants reported in this work among Chinese Uyghur children. Methods A comparative cross-sectional study was conducted. Subjects enrolled in the study were screened according to preset inclusion and exclusion criteria. The observer then obtained the dental age from the subjects’ panoramic radiographs based on the estimated rules of the London Atlas, Willems, and a new quick method. Paired t-test was used to compare the accuracy and precision of the above three estimation methods. Independent-sample t-test was used to find the difference between gender. Results Totally, 831 radiographs entered the analyses of this study. Among the three methods evaluated, the Willems method, in particular, showed a distinct underestimated tendency. The mean error of the dental age predicted by the London Atlas, the Willems method, and the quick method was 0.06 ± 1.13 years, 0.44 ± 1.14 years, and 0.30 ± 0.63 years, respectively. The mean absolute error was 0.86 ± 0.75 years according to the London Atlas, 1.17 ± 0.89 years under the Willems method, and 0.70 ± 0.54 years under our quick method. No significant difference was found between the chronological age and dental age using the London Atlas, generally for the 10 to 15 years group (p > 0.05), but our quick method for the 15–16 years children (p < 0.05) and Willems method (p < 0.001). Conclusion The London Atlas outperformed the Willems method with better accuracy and precision among 10–15 years Chinese Uyghur children. Our new quick method may be comparable to the London Atlas for children aged 10–14 and potentially become a more straightforward dental age prediction instrument.